Effects of Using Authentic Materials on Japanese Listening Ability of Third Year Japanese Major Students - Boonprakate, Chayanoot (Nimitmai Review Journal, 2021)
The objectives of this study were to compare the listening ability of third year Japanese major students before and after using authentic materials in Japanese Listening 2 course and to study the satisfaction of students toward implementation of authentic material in Japanese Listening 2 course. The population in this study consisted of 14 third year Thai Students majoring in Japanese who enrolled Japanese Listening 2 course in the second semester of the 2019 academic year at Thepsatri Rajabhat University. The investigation was executed forty-eight hours in sixteen weeks. The research instruments included sixteen lesson plans, five Japanese listening exercises, Japanese listening pre - posttests, and the questionnaire for analyzing the students’ attitude toward authentic material used in Japanese listening training. The data were statistically analyzed by means, standard deviation and percentage. The results of this study indicated that 1) the implementation of authentic material in Japanese listening course can enhance the students’Japanese listening ability at 14.84% and 2) the students’satisfaction toward the Japanese listening practice with authentic material was high in overall (µ=4.56)